Animal Models for the Study of the Relationships between Diet and Obesity: A Focus on Dietary Protein and Estrogen Deficiency - Chalvon-Demersay, Tristan; Blachier, François; Tomé, Daniel; Blais, Anne (Frontiers in Nutrition, 2017)
Obesity is an increasing major public health concern asking for dietary strategies to limit weight gain and associated comorbidities. In the present review, we present animal models, particularly rats and mice which have been extensively used by scientists to understand the consequences of diet quality on weight gain and health. Notably, modulation of dietary protein quantity and/or quality has been shown to exert huge effects on body composition homeostasis through the modulation of food intake, energy expenditure and metabolic pathways. Interestingly, the perinatal window appears to represent a critical period during which the protein intake of the dam can impact the offspring’s weight gain and feeding behavior. Animal models are also widely used to understand the processes and mechanisms which contribute to obesity under different physiological and pathophysiological stages. An interesting example of such aspect is the situation of decreased estrogen level occurring at menopause, which is linked to weight gain and decreased energy expenditure. To study metabolic disorders associated with such situation, estrogen withdrawal in ovariectomized animal models to mimic menopause are frequently used. According to many studies, clear species-specific differences exist between rats and mice that need to be taken into account when results are extrapolated to humans.